2023
DOI: 10.3847/2041-8213/acc334
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Gas Angular Momentum on the Formation of Magnetically Arrested Disks and the Launching of Powerful Jets

Abstract: In this letter, we investigate Bondi-like accretion flows with zero or low specific angular momentum by performing 3D general relativistic magnetohydrodynamic simulations. In order to check if relativistic jets can be launched magnetically from such flows, we insert a large-scale poloidal magnetic field into the accretion flow and consider a rapidly spinning black hole. We demonstrate that under such conditions the accretion flow needs to initially have specific angular momentum above a certain threshold to ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…In addition, [19] (BP) also showed that energy and angular momentum of the JCAP07(2024)075 infalling matter is magnetically removed by the field line and eventually carried off by the outgoing matter. Further, extensive numerical simulations of magnetohydrodynamic (MHD) accretion flow in both non-relativistic and relativistic regimes also confirm that jets/outflows are produced from accretion disk [20][21][22][23][24][25][26][27][28]. In particular, [20] reported that magnetic fields help in jet formation and its collimation process.…”
Section: Introductionmentioning
confidence: 92%
“…In addition, [19] (BP) also showed that energy and angular momentum of the JCAP07(2024)075 infalling matter is magnetically removed by the field line and eventually carried off by the outgoing matter. Further, extensive numerical simulations of magnetohydrodynamic (MHD) accretion flow in both non-relativistic and relativistic regimes also confirm that jets/outflows are produced from accretion disk [20][21][22][23][24][25][26][27][28]. In particular, [20] reported that magnetic fields help in jet formation and its collimation process.…”
Section: Introductionmentioning
confidence: 92%
“…Meanwhile, the AGN disk would be magnetized, with a ratio of ambient gas to magnetic pressure β  10-100 (King et al 2007;Salvesen et al 2016;Kaaz et al 2023a). Recent numerical simulations indicate that the ambient magnetic fields are frozen and flow inward with gas, resulting in their accumulation to saturation near the BH (Kaaz et al 2023a;Kwan et al 2023). Due to a large spin of the merger remnant (e.g., Tichy & Marronetti 2008;, a jet would be generated via the Blandford-Znajek (BZ) mechanism (Blandford & Znajek 1977), the power of which can be estimated as…”
Section: Formation and Power Of Bh-driven Jetmentioning
confidence: 99%
“…If either embedded black hole has an appreciable spin, jets will likely be launched into the AGN disk. Because jet efficiency strongly depends on the angular momentum of the gas accreting onto a given black hole (e.g., Kwan et al 2023), it seems probable that prograde binaries could support jets; on the other hand, because the CSD size of retrograde binaries appears to depend strongly on softening, if they exist at all (Li & Lai 2022), retrograde binaries may not be able to launch strong jets. Although on small scales jets are typically aligned with the spin of the black hole by which they are launched, on larger scales jets can be aligned with the accretion disk surrounding them (McKinney et al 2013;Liska et al 2018).…”
Section: Accretionmentioning
confidence: 99%